Pendekatan estetika pada desain pesan multimedia pembelajaran - Pranata, Moeljadi (Bahasa dan Seni: Jurnal Bahasa, Sastra, Seni, dan Pengajarannya, 2013)
The development of multimedia design is influenced by various theories, such as visual aesthetic principles. Aesthetic principles are used to guide the design process and play a role in increasing the attractiveness of messages. However, along with advances in computer graphics, the application of graphic design aesthetics in multimedia learning has led to the concept of multimedia performance that is entertaining and aesthetically oriented. In addition, this technological development, together with multimedia technology, has expanded the professional scope of multimedia learning design beyond the field of education to include professions such as graphic design.